If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -2 = -9 + -2y Reorder the terms: -2 + 5y = -9 + -2y Solving -2 + 5y = -9 + -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. -2 + 5y + 2y = -9 + -2y + 2y Combine like terms: 5y + 2y = 7y -2 + 7y = -9 + -2y + 2y Combine like terms: -2y + 2y = 0 -2 + 7y = -9 + 0 -2 + 7y = -9 Add '2' to each side of the equation. -2 + 2 + 7y = -9 + 2 Combine like terms: -2 + 2 = 0 0 + 7y = -9 + 2 7y = -9 + 2 Combine like terms: -9 + 2 = -7 7y = -7 Divide each side by '7'. y = -1 Simplifying y = -1
| 15x^2-25x^3=0 | | -(3a-5b+5c)= | | 65+x(x-5)=180 | | -7x-15+9x+23=2 | | r/2=11/8 | | 10b-2=4b-14 | | -(5x-10)=5 | | -5+2x-7x=35 | | a=160m+215 | | 4x-22=2x+12 | | -4m+2+1m=23 | | 2p-3=7 | | 15m+4-9m= | | -3x-7x=97 | | 6x+6=-x+55 | | 0.5=0.4y-0.25y | | 2x+6=4x+12 | | 3(-3x-2)-4x-5=-3 | | 5x-2x=168 | | .4(x-12)=1.2(x-4) | | 2(3a-4.2)=5a | | 6g-9/3=g | | 4(m+1)-2(3m+1)=-3(m-7)+5 | | z-2/3=1/8 | | 3(s+1)-5=3s-2 | | 5x-27=-4x | | -4-5x=7-x | | 5x+9+8=4 | | 2.85s-7=12.85s-2 | | ax+by=c(y) | | 2(x+5)+3= | | 2.5(x-2)-6=9 |